Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with prognosis of estrogen receptor-negative breast cancer after chemotherapy. Issue 1 (December 2015) - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten; Rafiq, Sajjad; Behrens, Sabine; Goode, Ellen; Pharoah, Paul; Seibold, Petra; Fasching, Peter; Andrulis, Irene; Kristensen, Vessela; Couch, Fergus; et al.
Abstract Introduction Tumor lymphocyte infiltration is associated with clinical response to chemotherapy in estrogen receptor (ER) negative breast cancer. To identify variants in immunosuppressive pathway genes associated with prognosis after adjuvant chemotherapy for ER-negative patients, we studied stage I-III invasive breast cancer patients of European ancestry, including 9, 334 ER-positive (3, 151 treated with chemotherapy) and 2, 334 ER-negative patients (1, 499 treated with chemotherapy). Methods We pooled data from sixteen studies from the Breast Cancer Association Consortium (BCAC), and employed two independent studies for replications. Overall 3, 610 single nucleotide polymorphisms (SNPs) in 133 genes were genotyped as part of the Collaborative Oncological Gene-environment Study, in which phenotype and clinical data were collected and harmonized. Multivariable Cox proportional hazard regression was used to assess genetic associations with overall survival (OS) and breast cancer-specific survival (BCSS). Heterogeneity according to chemotherapy or ER status was evaluated with the log-likelihood ratio test. Results Three independent SNPs inTGFBR2 andIL12B were associated with OS (P <10−3 ) solely in ER-negative patients after chemotherapy (267 events). Poorer OS associated withTGFBR2 rs1367610 (G > C) (per allele hazard ratio (HR) 1.54 (95% confidence interval (CI) 1.22 to 1.95), P  = 3.08 × 10−4 ) was not found in ER-negative patients without chemotherapy or ER-positive patients with chemotherapy (P for interaction <10−3 ). Two SNPs inIL12B (r2  = 0.20) showed different associations with ER-negative disease after chemotherapy: rs2546892 (G > A) with poorer OS (HR 1.50 (95% CI 1.21 to 1.86), P  = 1.81 × 10−4 ), and rs2853694 (A > C) with improved OS (HR 0.73 (95% CI 0.61 to 0.87), P  = 3.67 × 10−4 ). Similar associations were observed with BCSS. Association withTGFBR2 rs1367610 but notIL12B variants replicated using BCAC Asian samples and the independent Prospective Study of Outcomes in Sporadic versus Hereditary Breast Cancer Study and yielded a combined HR of 1.57 ((95% CI 1.28 to 1.94), P  = 2.05 × 10−5 ) without study heterogeneity. Conclusions TGFBR2 variants may have prognostic and predictive value in ER-negative breast cancer patients treated with adjuvant chemotherapy. Our findings provide further insights into the development of immunotherapeutic targets for ER-negative breast cancer.